2017
DOI: 10.3389/fmicb.2016.02150
|View full text |Cite
|
Sign up to set email alerts
|

Tracing of Two Pseudomonas Strains in the Root and Rhizoplane of Maize, as Related to Their Plant Growth-Promoting Effect in Contrasting Soils

Abstract: TaqMan-based quantitative PCR (qPCR) assays were developed to study the persistence of two well-characterized strains of plant growth-promoting rhizobacteria (PGPR), Pseudomonas fluorescens Pf153 and Pseudomonas sp. DSMZ 13134, in the root and rhizoplane of inoculated maize plants. This was performed in pot experiments with three contrasting field soils (Buus, Le Caron and DOK-M). Potential cross-reactivity of the qPCR assays was assessed with indigenous Pseudomonas and related bacterial species, which had bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 72 publications
2
27
0
Order By: Relevance
“…Consequently, depending on the properties of the soil and the structure of the naturally occurring rhizosphere community, their plant growth-promoting effect has often shown limited reproducibility. As reported in Mosimann [25], soil properties such as pH can have impacts on the BEs' ability to exert plant growth-promoting effects. Moreover, the amount of total and plant available P seems to be a decisive factor for the performance of bacterial BEs [26,27].…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Consequently, depending on the properties of the soil and the structure of the naturally occurring rhizosphere community, their plant growth-promoting effect has often shown limited reproducibility. As reported in Mosimann [25], soil properties such as pH can have impacts on the BEs' ability to exert plant growth-promoting effects. Moreover, the amount of total and plant available P seems to be a decisive factor for the performance of bacterial BEs [26,27].…”
Section: Introductionmentioning
confidence: 87%
“…The strain Pseudomonas DSMZ 13134 is an efficient root colonizer [38] and has been shown to solubilize inorganic phosphate under in vitro conditions [39]. Moreover, it has recently shown the potential to improve plant growth and phosphorus acquisition when inoculated to maize [10,25]. The gram-positive strain Bacillus amyloliquefaciens FZB42 is mainly studied for its biocontrol potential but other studies also indicate its ability to act as a biofertilizer [40,41].…”
Section: Be Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study also showed that soil zones around NH 4 + -depots with high root densities may be sites for effective root colonization by inoculated PGPMs. Nevertheless, in addition to cultures on selective media, molecular tracing techniques like qPCR [34] as already shown for Pseudomonas sp. DSMZ 13134 would provide more precision in tracing.…”
mentioning
confidence: 99%
“…Plant inoculation with beneficial bacteria, as the Pseudomonas strain used in this study, are known to induce changes in plant architecture due to modification of the plant endogenous hormonal balance (Mosimann et al 2016;Calvo et al 2017). The potential of Pseudomonas AZM-01 and derivative EDA-resistant mutants to produce auxins was demonstrated in the presented study, and this trait should be related to the modifications on roots of plants inoculated with the wild and mutant strains.…”
Section: Discussionmentioning
confidence: 73%